How flexible are wages in response to local unemployment in South Africa? - Kingdon, G; Knight, J (GPRG, 2005)
It is commonly claimed that the South African labor market is unusually inflexible owing to the strength of the unions and the system of centralized collective bargaining. One aspect of labor market inflexibility concerns the responsiveness of wages to local unemployment. Examining this spatial relationship, we find that the elasticity of wages to local unemployment rates in South Africa is -0.1, similar to that found in other countries, including the US and the UK. This is striking because South Africa has a national unemployment rate of over 30%. We find that the wage curve elasticity persists over a much wider range of unemployment rates than in OECD countries, implying that unemployment in South Africa can have a large impact on wages.